2011
DOI: 10.1186/2047-783x-16-7-315
|View full text |Cite
|
Sign up to set email alerts
|

Guideline-adherent initial intravenous antibiotic therapy for hospital-acquired/ventilator-associated pneumonia is clinically superior, saves lives and is cheaper than non guideline adherent therapy

Abstract: IntroductionHospital-acquired pneumonia (HAP) often occurring as ventilator-associated pneumonia (VAP) is the most frequent hospital infection in intensive care units (ICU). Early adequate antimicrobial therapy is an essential determinant of clinical outcome. Organisations like the German PEG or ATS/IDSA provide guidelines for the initial calculated treatment in the absence of pathogen identification. We conducted a retrospective chart review for patients with HAP/VAP and assessed whether the initial intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 29 publications
(29 reference statements)
3
48
0
3
Order By: Relevance
“…While several studies on adherence to guidelines of empirical antibiotic therapy for CAP have been conducted in medical wards and intensive care units [6,[13][14][15], a relatively small number of studies have investigated adherence in patients with healthcare-associated pneumonias such as HAP or HCAP [7,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…While several studies on adherence to guidelines of empirical antibiotic therapy for CAP have been conducted in medical wards and intensive care units [6,[13][14][15], a relatively small number of studies have investigated adherence in patients with healthcare-associated pneumonias such as HAP or HCAP [7,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In another multicenter trial with 740 mechanically ventilated patients, combination therapy with meropenem and ciprofloxacin increased the likelihood of appropriate empiric therapy in VAP for those with MDR pathogens (84.2 vs. 18.8 %, p \ 0.001), but had no impact on mortality; however, in this population, MDR pathogens were uncommon [44]. In a study with initial empiric antibiotic therapy based on the German PEG guidelines, clinical improvement occurred in 82 % of the guideline-adherent group compared to 47 % in the non-adherent group (p = 0.001), with better survival in the guideline-adherent group (86 vs. 74 %, p = 0.021) [45].…”
Section: Treatment Of Vapmentioning
confidence: 99%
“…Resistant infections may lead to treatment failures and the need to use second or third-line antibiotics, increased length of stay, and/or mortality. Studies have also demonstrated that healthcare resource utilization typically rises with failure of initial empiric therapy [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%